2015
DOI: 10.5513/jcea01/16.4.1657
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil moisture content and tractor wheeling intensity on traffic-induced soil compaction

Abstract: Soil compaction causes deleterious effects on physical and mechanical proprieties of agricultural soils. In order to investigate the effect of soil moisture content and tractor wheeling intensity on traffic-induced soil compaction, this study was carried out on a field with clay loam soil. Soil dry bulk density and hydraulic conductivity as well as emergence percentage of corn seedlings and dry mass of the sampled mature plants were considered the dependent variables of the experiment. Independent variables co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Conversely gradual increase in bulk density with an increase in soil moisture content was already documented by Ref. [ 33 ]. Reference [ 15 ] noted increase in bulk density and penetration resistance within no-till.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Conversely gradual increase in bulk density with an increase in soil moisture content was already documented by Ref. [ 33 ]. Reference [ 15 ] noted increase in bulk density and penetration resistance within no-till.…”
Section: Discussionsupporting
confidence: 63%
“…[ 33 ] also observed that wheel traffic caused an increase in soil bulk density though wheels are loaded in flooded condition. In the present study also, when the harvester and seed drill was employed, the soil moisture was optimum.…”
Section: Discussionmentioning
confidence: 99%
“…Some initial compaction facilitated these cultivar-dependent differences in soil resistance, with rainfall furthering compacting the topsoil ( Augeard et al., 2008 ), preventing tuber expansion increasing soil height. Furthermore, as dryer soils are less susceptible to compaction ( Ahmadi and Ghuar, 2015 ), soil resistance in the dryer uncompacted plots changed less as tuber biomass increased ( Figures 4 , 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tillage alters the physical characteristics of soil, significantly affecting its aeration, nutrient levels, and biological activity, but also water-holding capacity and hence temperature regulation. The effects on soil water content and flow are closely linked to the resulting compaction [199] caused by the forces exerted by the tractor wheels and tillage equipment, especially when they operate under a particular range of intermediate soil water contents, which render the soil highly susceptible to deformation [200,201]. Almost all types of tires result in increased soil compaction within the wheel tracks, although there may be differences depending on tire pressure [202].…”
Section: How Agricultural Traffic and Tillage Affect Soil Compactionmentioning
confidence: 99%